Impact evaluation for policy making: a close look at Latin American countries with weaker research capacities - Alzua, Maria Laura (2012)
Interest in Impact Evaluation (IE) has grown rapidly in Latin America and the Caribbean. However, rigorous impact evaluations are still very much concentrated in a few countries. This review looks at the way impact evaluation studies are being produced and used for policy making in a sample of countries in the region that are a priori considered less capable to absorb the current trend observed in other more developed countries in the region. This study is threefold: (i) we performed a systematic search for the studies that evaluate the impacts of programs and policies with sound identification strategies. Then we analyzed time trends and the key actors in the demand, production and funding of the studies. We also (ii) carried out three case studies (of the Dominican Republic, El Salvador and Peru) to explore the institutional factors that work in favor and against the demand and use of rigorous impact evaluations for policy making, and (iii) we searched and identified training activities for the promotion of IEs, and their role in shaping policies and programs.